A novel enterocyte-related 4-gene signature for predicting prognosis in colon adenocarcinoma - Cheng, Xuehua; Wei, Yong; Fu, Yugang; Li, Jiacheng; Han, Li (Frontiers in Immunology, 2022)
Colon adenocarcinoma (COAD) is a fatal disease, and its cases are constantly increasing worldwide. Further, the therapeutic and management strategies for patients with COAD are still unsatisfactory due to the lack of accurate patient classification and prognostic models. Therefore, our study aims to identify prognostic markers in patients with COAD and construct a cell subtype-specific prognostic model with high accuracy and robustness. We found that the proportion of epithelial cells was obviously large in COAD samples. Subsequent analysis of epithelial cells showed that enterocyte had the highest activity in the communication network and had responses at the early stage of epithelial differentiation. Based on enterocyte data, 30 ERDEGs were identified and a 4-gene prognostic model including CPM, CLCA4, ELOVL6, and ATP2A3 was developed and validated. The risk score derived from this model was considered as an independent variable factor to predict overall survival. It was adopted to divide patients into high- and low-risk groups, and the relationship between the risk score and immune infiltration, immunotherapy response, immune status, clinical characteristics, and drug sensibility was tested. Finally, IHC analysis confirmed the expression of signature genes.In this study, we developed and validated a novel prognostic signature, which is able to predict the response to immunotherapy in COAD patients. More importantly, this model provides useful insight to the management of colon cancer patients and precision medicine.